Children with familial hypercholesterolemia display changes in LDL and HDL function: A cross‐sectional study. (19th October 2021) - Christensen, Jacob J.; Narverud, Ingunn; Ruuth, Maija; Heier, Martin; Jauhiainen, Matti; Ulven, Stine M.; Bogsrud, Martin P.; Kovanen, Petri T.; Halvorsen, Bente; Oda, Michael N.; Wium, Cecilie; Retterstøl, Kjetil; et al.
Abstract: Background: The functional status of lipoprotein particles contributes to atherogenesis. The tendency of plasma low‐density lipoprotein (LDL) particles to aggregate and the ability of igh‐density lipoprotein (HDL) particles to induce and mediate reverse cholesterol transport associate with high and low risk for cardiovascular disease in adult patients, respectively. However, it is unknown whether children with familial hypercholesterolemia (FH) display lipoprotein function alterations. Hypothesis: We hypothesized that FH children had disrupted lipoprotein functions. Methods: We analyzed LDL aggregation susceptibility and HDL‐apoA‐I exchange (HAE), and activity of four proteins that regulate lipoprotein metabolism (cholesteryl ester transfer protein, lecithin–cholesterol acyltransferase, phospholipid transfer protein, and paraoxonase‐1) in plasma samples derived from children with FH ( n = 47) and from normocholesterolemic children ( n = 56). Variation in lipoprotein functions was further explored using an nuclear magnetic resonance‐based metabolomics profiling approach. Results: LDL aggregation was higher, and HAE was lower in FH children than in normocholesterolemic children. LDL aggregation associated positively with LDL cholesterol (LDL‐C) and negatively with triglycerides, and HAE/apoA‐I associated negatively with LDL‐C. Generally, the metabolomic profile for LDL aggregation was opposite of that of HAE/apoA‐I. Conclusions: FH children displayed increased atherogenicity of LDL and disrupted HDL function. These newly observed functional alterations in LDL and HDL add further understanding of the risk for atherosclerotic cardiovascular disease in FH children. Abstract :